Da'wah Transformation Through Malay Literature: : A Case Study of the Use of Hikayat and Poetry by Sheikh Abdul Qodir al-Mandily - Riski Angga Putra (Fakultas Dakwah dan Komunikasi UIN Sunan Kalijaga, 2024)
This study explores the use of hikayat and rhymes by Sheikh Abdul Qodir al-Mandily in his da'wah, focusing on how this method utilizes local cultural elements to effectively convey Islamic teachings to the Malay community. Sheikh Abdul Qodir al-Mandily, a Malay scholar, used this traditional literary form to align religious messages with the culture known and accepted by his audience, thus making it easier to understand and accept the teachings of Islam.The results of the study show that the use of sagas and rhymes not only makes the message of da'wah more relevant and easy to understand but also strengthens the emotional connection between the community and religious teachings. Hikayat, with its narrative of stories full of moral values, and rhyme, with its traditional poetic structure, serves as an effective medium in conveying Islamic teachings in a way that can be accepted and internalized by the audience.This approach has proven to remain relevant in the context of contemporary da'wah, despite the development of technology and modern media. This culture-based method offers a valuable model for future preachers in adapting to their local cultural context. This study recommends further exploration of the application of culture-based da'wah methods in other cultural contexts and in-depth studies of the long-term impact of the use of these methods on social and religious change.